The role of wakf in financing higher education – an analysis of the implementation of educational wakf in Johor - Mohd Roslan, Nur Razan Izzati; Nor Muhamad, Nasrul Hisyam; Che Yaacob, Ahmad; A Rahman, Siti Nur Hadis (2023)
The increase in socioeconomic and current development has had an impact on the increasing cost of education year by year. In the long run, the rising cost of education will have a negative impact on generating a knowledge society. Wakf has proven to be an important tool for improving Muslim quality of life in a variety of ways, including education. Thus, the UTM Education Wakf Fund and UTHM Education Cash Wakf Fund have been established, and both universities have been appointed as the special Nazir (Special Trustee) by the Johor State Islamic Religious Council. This wakf was established in accordance with the Minister of Higher Education's recommendation that higher education institutions create their education wakf. This paper aims to analyze wakf management fund practices at UTM and UTHM. The research is qualitative and uses content analysis by looking at the management responsible for administering wakf funds in higher education institutions. The research findings show that the administration of the wakf for education fund is characterized by a systematic and effective approach, as well as an adoption of proactive fundraising methods. The findings of this paper will benefit other educational institutions such as madrasahs, maahad tahfiz, and schools in developing a wakf fund by using the management of the wakf system in higher education institutions as a model.